Analysis of fiscal decentralisation, human development, and regional economic growth in indonesia - Eleonora Sofilda; Muhammad Zilal Hamzah; Suhal Kusairi (Cogent Economics & Finance, 2023)
In Indonesia, fiscal decentralisation has been implemented for two decades, and it is expected that the regions will have a sufficient level of independence to increase economic growth and welfare. This study investigates the influence of fiscal decentralisation and human development on regional economic growth. The sample data comprised 484 county-level in Indonesia and utilised the panel data method. The findings showed that the central government grant, locally generated revenue, and human capital development positively influenced regional economic growth, although the degree of decentralisation negatively affected regional growth. Meanwhile, for regions with independence above 50 per cent, decentralisation, locally generated revenue, central government transfer and provincial loans and human capital development positively influenced regional economic growth. In addition, findings also indicated that a dynamic effect exists, implying that the performance of previous regional economic growth influenced current economic achievements. The policy implication of the study is that policymakers cannot equalise policy to boost regional economic growth because every county has its specific characteristics.
Keywords: H4; H7; O15; O18; 330; Economic Growth; Financial Independence; Fiscal Decentralisation; Human Capital Development